Adaptation of the teacher as social context questionnaire in the Indonesian higher education context - Meilani Rohinsa (Personifikasi: Jurnal Ilmu Psikologi, 2026)
Understanding students’ perceptions of lecturer support is essential to advancing motivation and engagement in higher education. The Teacher as Social Context Questionnaire (TASCQ), grounded in Self-Determination Theory, has been widely applied across diverse contexts; however, robust psychometric validation in Indonesian higher education remains largely absent. Addressing this gap, this study provides one of the first rigorous cross-cultural adaptations of the TASCQ short form and systematically evaluates its psychometric properties. Using a quantitative design, the 24-item TASCQ short form was administered to 200 students from public and private universities. Construct validity and reliability were examined using Confirmatory Factor Analysis (CFA). The results indicated that 18 items met validity criteria, with standardized loading factors ranging from 0.504 to 0.842. Reliability analysis demonstrated a strong internal consistency (CR = 0.855; VE = 0.812). Theoretically, these findings extend the applicability of Self-Determination Theory within a collectivist cultural context which contributes to the growing body of cross-cultural validation research in higher education. Practically, the validated Indonesian version of the TASCQ short form offers a robust instrument to inform evidence-based education policy, strengthen lecturer professional development, and enhance student-centered learning practices in Indonesia.